Penerapan Media Ular Tangga dalam Pembelajaran Matematika - Kharismatika, Afenstya Happy; Fajriah, Khusnul; Rahayu, Lilik Puji (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of the research is to evaluate the impact of using this media on students' understanding of mathematical concepts and learning motivation. The research method used is analysis using descriptive qualitative methods. The implications of this research highlight the importance of using interactive media in improving mathematics learning outcomes at the initial level of basic education. This study evaluates the effectiveness of implementing snakes and ladders media in mathematics learning for grade 1 elementary school students. Through a descriptive analysis approach, this research observed an increase in understanding of mathematical concepts and students' level of learning motivation. The results show that the use of snakes and ladders media makes a significant positive contribution to students' understanding of mathematical concepts and learning motivation compared to conventional methods.